Psychological and Physiological Processes in Figure-Tracing Abilities Measured Using a Tablet Computer: A Study with 7 and 9 Years Old Children - Giammarco, Enrico; Di Sano, Sergio; Aureli, Tiziana; Cerratti, Paola; Fanò-Illic, Giorgio; Pietrangelo, Tiziana (Frontiers in Psychology, 2016)
The present study investigated the use of a tablet computer to assess figure-tracing skills and their relationships with psychological (visual–perceptual processes, cognitive processes, handwriting skills) and physiological (body mass index, isometric strength of arms) parameters with school-children of second (7-8-year-olds) and fourth (9-10-year-olds) grades. We were also interested in gender differences. The task required tracing of geometric figures on a template, shown on a tablet screen in light grey, for the segments that make up the target figure, one at a time. This figure-tracing tablet test allows acquisition and automated analysis of four parameters: number of strokes (pen lift) for each segment; oscillations of lines drawn with respect to reference lines; pressure of pen on tablet; and average speed of tracing. The results show a trade-off between speed and quality for the tablet parameters, with higher speed associated with more oscillations with respect to the reference lines, and lower number of strokes for each segment, in both male and female children. The involvement of visual–motor integration on the ability to reduce the oscillations in this tablet test was only seen for the male children, while both the male and female children showed a relationship between oscillations and more general/ abstract visual–spatial processes. These data confirm the role of visual–motor processes in this figure-tracing tablet test only for male children, while more general visual–spatial processes influence the performance in the tablet test for both sexes. We conclude that the test proposed is useful to screen for grapho-motor difficulties.